Swift J0513.4-6547 in outburst - Sturm, R.; Carpano, S.; Haberl, F.; Maggi, P.; Vasilopoulos, G. (2014)
We report an outburst of Swift J0513.4-6547, a 27.28 s pulsar Be/X-ray binary in the Large Magellanic Cloud, which was discovered by Krimm et al. (2009, ATel #2011) and has an orbital period of 27 d (ATel #5511).
Keywords: Binary; Neutron Star